The incredible Incas and their timeless land - McIntyre, Loren, 1917-; National Geographic Society (U.S.). Special Publications Division (Washington : National Geographic Society, 1975)
A history of the Inca Empire and its expansion duringthe 15th and 16th centuries until its conquest by theSpanish under Francisco Pizarro.
Silent strings -- Sons of the sun -- Lord Inca cataclysm -- Unforgettable one -- War between the brothers -- Invaders from an alien world -- Eclipse of the sun -- Lost empire.
Includes bibliographical references (p. 198) and index.
Keywords: Incas; Peru -- Antiquities; Peru -- Description and travel